Development of integrated system of scientific periodicals based on the OJS - Kudim, K.A.; Reznichenko, V.A.; Novitsky, A.V.; Proskudina, G.Yu.; Ovdii, O.M. (Інститут програмних систем НАН України, 2017)
The paper discusses the basic facilities of OJS open sourse system as a platform of management and electronic publishing of scientific journals. This system allows publishers to deploy journal sites focused on the full life cycle of scientific journals with a mi-nimum expenditures and facilitates journal representation in international analytic databases such as such as Scopus.